Mathematics competitions, a perspective from Puerto Rican teaching - Cáceres, Luis; Henao, Ferney (Universidad Antonio Nariño, 2023)
This article summarizes the findings found in a study carried out with mathematics teachers, at the secondary level, from public and private schools in Puerto Rico. The main objective is to understand and characterize the vision that Puerto Rico math teachers have about math competitions and the participation of their students in them. The study aims to analyze the impact that math competitions have on teachers and their students as part of teaching-learning strategies. In this study, 213 teachers from different regions of the island participated.